Educação Especial e pandemia da Covid-19: o caso da Rede Municipal de educação de Vila Velha/ES - Souza, Francisca Kátia Barbosa de (2023)
This Master's study in Education in the professional modality aims to understand the actions implemented by the Municipal Education Network of Vila Velha/ES to meet the schooling needs of students with disabilities during the Covid-19 pandemic and for the return to in-person activities, considering the promotion of the social right to Education. To this end, it sets the following specific objectives: a) understand the protocols adopted at the national and local level to address the Covid-19 pandemic; b) analyze the protocols established by the Municipal Education Network of Vila Velha/ES for the schooling of students during the social isolation period caused by the Covid-19 Pandemic; c) create a listening network with professionals from the Municipal Education Network of Vila Velha/ES to understand the movements produced for the schooling of students with disabilities during the pandemic period and for the return to face-to-face teaching. It adopts as a theoretical reference authors who discuss the social right to Education, others dedicated to theorizing about Special Education, and researchers who have focused on producing knowledge about the impacts of the Covid-19 pandemic in educational contexts. Theoretically and methodologically, it is based on qualitative assumptions and exploratory research, gathering data through the presentation of the study to the competent bodies for authorization; document consultation related to Special Education in the investigated Teaching Network; conducting semi-structured interviews with Special Education teachers from educational units in Vila Velha/ES and the general coordinator of the sector. It uses a field diary and an app that was specifically developed for conducting interviews in February/March 2023, selecting as participants five Special Education teachers and the coordination of the department. As results, it can be seen that the investigated Municipal Education Network followed the national trend and sought to implement actions for the continuity of the educational process of the students through emergency remote teaching, using a platform, printed activities, and contacts via social networks, WhatsApp, among others. In addition, investments in teacher training and the provision of financial resources for these professionals to acquire technological resources are noted. Also highlighted is the partnership between school and family in guiding the students' formative process during the pandemic. Challenges also crossed the process, such as the lack of technological resources in the homes of students and teachers; difficulties for teachers to use technologies as a pedagogical tool and the production of a greater distortion in the age-content-grade relationship. The implemented alternatives and the mentioned barriers were also present in the context of Special Education, calling the Teaching Network to implement actions to face issues that the pandemic and emergency remote teaching left in the schooling of these students. As an Educational Product, this study presents the development of an app called 'Educai', which aims to enable families of students targeted by Special Education to follow the records of these students' school lives through a smartphone/tablet.